Fraksinasi dan karakterisasi asap cair dari kayu ulin (Eusideroxylon zwageri Teijsm. & Binn.) sebagai pelarut kitosan - Ahmad Budi Junaidi (Jurnal Riset Industri Hasil Hutan, 2019)
The purpose of this reseach was to study the solubility of chitosan in liquid smoke as a preliminary study of the application of a combination of liquid chitosan as a bioimmunizer and growth booster in plants.Fractionation and characterization of liquid smoke from ulin wood (Eusideroxylon zwageri Teijsm. & Binn.) and its ability test as chitosan solvent have been performed. Fractional distillation done using a set of tools distillation each fraction,fraction 1 (≤100° C), the fraction 2 (101-120° C), and fraction 3 (121-140°C). The resulting liquid smoke was then measured degree of acidity, the total acid analysis, the specific gravity, chitosan solubility test in liquid smoke. The result of the research showed that the liquid smoke recovery value of fractionation distillation of each fraction was 54.91; 29.39; and 8.8 (%). The result of liquid smoke characterization of each fraction obtained pH value fraction 1, fraction 2, and fraction 3 are respectively 2.33; 2.14; and 2.08, the total acid was 2.97; 4.59; and 8.88 (% g/mL), the specific gravity was 1,005; 1,006; and 1.009, and the phenol content was respectively 2.06; 3.67; and 2.30 (g/L). The solubility of chitosan in liquid smoke increasing with the concentration of each liquid smoke fraction and 5% (v/v) of liquid smoke concentration was able to dissolve chitosan more than 50 g/L.